Proteome-wide identification of S-sulfenylated cysteines reveals metabolic response to freezing stress after cold acclimation in Brassica napus - Yu, Liangqian; Dai, Zezhang; Zhang, Yuting; Iqbal, Sidra; Lu, Shaoping; Guo, Liang; Yao, Xuan (Frontiers in Plant Science, 2022)
Redox regulation plays a wide role in plant growth, development, and adaptation to stresses. Sulfenylation is one of the reversible oxidative post-transcriptional modifications. Here we performed an iodoTMT-based proteomic analysis to identify the redox sensitive proteins in vivo under freezing stress after cold acclimation in Brassica napus. Totally, we obtained 1,372 sulfenylated sites in 714 proteins. The overall sulfenylation level displayed an increased trend under freezing stress after cold acclimation. We identified 171 differentially sulfenylated proteins (DSPs) under freezing stress, which were predicted to be mainly localized in chloroplast and cytoplasm. The up-regulated DSPs were mainly enriched in photosynthesis and glycolytic processes and function of catalytic activity. Enzymes involved in various pathways such as glycolysis and Calvin-Benson-Bassham (CBB) cycle were generally sulfenylated and the metabolite levels in these pathways was significantly reduced under freezing stress after cold acclimation. Furthermore, enzyme activity assay confirmed that the activity of cytosolic pyruvate kinase and malate dehydrogenase 2 was significantly reduced under H2O2 treatment. Our study provides a landscape of redox sensitive proteins in B. napus in response to freezing stress after cold acclimation, which proposes a basis for understanding the redox regulation in plant metabolic adaptation to freezing stress after cold acclimation.